Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - Yeo, In Seok; Go, Kang Seok; Jeon, Woo Young; Jang, Min Jeong; Lee, Hye Jeong; Seo, Sung Hwa; Kim, Young Su; Park, Hyun A.; Min, Byung wook; Park, Kyungmoon; Yang, Yung Hun; Choi, Kwon Young; et al. (Journal of Cleaner Production, 2024)
The growing accumulation of plastic waste poses a pressing environmental challenge. Traditional disposal methods, such as incineration and landfilling, carry considerable health and ecological risks. In response, our study presents an innovative method to repurpose mixed plastic waste into valuable α,ω-diacids utilizing chemo-biological processes. We extracted pyrolysis oil, rich in hydrocarbons spanning a broad range of chain lengths (C7 to C32), from household plastic waste and employed a genetically engineered β-oxidation-blocked Candida tropicalis strain to convert this oil into α,ω-diacids of various chain lengths. Simple distillation at 200 °C enabled the extraction of medium-chain hydrocarbons from the pyrolysis oil. However, an increased ratio of medium-chain alkenes posed a toxicity challenge to the cells. Through hydrogenation, these medium-chain alkenes were fully converted to alkanes. Remarkably, cell growth was maintained even with an 8% concentration of hydrogenates. The subsequent biotransformation yielded medium-chain diacids, with 94.3% of the produced α,ω-diacids being of medium-chain length (C7 to C14). These results offer a novel and scalable solution for converting everyday plastic waste into valuable chemicals, thus significantly contributing to the circular economy and the advancement of sustainability goals.
Keywords: Biological technology; Candida tropicalis; Chains length; Chemical and biologicals; Chemical technologies; Microbial biotransformations; Plastic waste upcycling; Plastics waste; Pyrolysis oil; Α,ω-diacid; Candida tropicalis; Microbial biotransformation; Plastic waste upcycling; Pyrolysis oil; Sustainability; α,ω-diacids